Molecular regulation of the training response: New techniques to study old questions - Ordway, G. A. (European Journal of Sport Science, 2001)
Exercise training provides a powerful tool with which to study the adaptive capacity of tissues, organ systems, and organisms. A rich literature from a number of disciplines gives strong evidence that exercise training is perhaps the best chronic physiological stress for the study of human or animal function. It is a stress the allows one to look not only at how individual systems respond but also how they interact in providing an overall response. Although much is known about the adaptations to exercise training, we are only beginning to understand molecular mechanisms that regulate the responses to training. This summary paper will present some basic concepts regarding these molecular mechanisms and their role in the training response in skeletal muscle, followed by some examples of how these new techniques are being used to study old questions.